2015
DOI: 10.1186/s12955-015-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life and related factors among residents in a disaster area of the Great East Japan Earthquake and giant tsunami

Abstract: BackgroundOral health is one of the most important issues for disaster survivors. The aim of this study was to determine post-disaster distribution of oral health-related quality of life (OHRQoL) and related factors in survivors of the Great East Japan Earthquake and Tsunami.MethodsQuestionnaires to assess OHRQoL, psychological distress, disaster-related experiences, and current systemic-health and economic conditions were sent to survivors over 18 years of age living in Otsuchi, one of the most severely damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 28 publications
(38 reference statements)
1
60
0
Order By: Relevance
“…1 ). Detailed methods of initial subject recruitment were reported in our previous paper [ 24 ]. All the candidates gave informed consent to participate in this study after receiving sufficient information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Detailed methods of initial subject recruitment were reported in our previous paper [ 24 ]. All the candidates gave informed consent to participate in this study after receiving sufficient information.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the rate of growth of the elderly population has rapidly increased due to the outflow of the younger generation in post-disaster areas, and a considerable number of elderly people are still displaced from their homes 5 years after the disaster [ 21 ]. The extraordinary lifestyle after the disaster has had negative effects on systemic, mental, and oral health [ 22 24 ], and could affect the prevalence of oral Candida colonization in elderly community dwellers in the disaster areas.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Following transient psychological distress, the risk of depression and insomnia were commonly increased. [11][12][13] The field of disaster dentistry could play supportive roles in management of postdisaster distress among disaster survivors, 14,15 as supported by the report of Kishi et al 13 indicating that serious psychological distress among GEJE survivors was strongly associated with lower oral health-related quality of life. Similarly, our previous reports indicated the increase in oral problems including subjective toothache among the GEJE survivors, with robust associations with psychological distress and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Natural disasters cause many public health problems owing to the sudden environmental changes associated with the collapse of social systems . Following transient psychological distress, the risk of depression and insomnia were commonly increased . The field of disaster dentistry could play supportive roles in management of postdisaster distress among disaster survivors, as supported by the report of Kishi et al indicating that serious psychological distress among GEJE survivors was strongly associated with lower oral health‐related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The oral health-related quality of life is known to be affected by many factors [ 14 ], but no marked differences by gender have been noted in previous reports on the development of assessment indices using this study [ 14 , 27 ]. However, some studies have reported that gender affected[ 28 , 29 ] the oral health-related quality of life. For example, female have shown a tendency to have a low oral health-related quality of life [ 28 ].…”
Section: Discussionmentioning
confidence: 99%